KONTROVERSI PENUNDAAN PEMILIHAN KEPALA NEGARA PERSPEKTIF FIQH SIYASAH (Studi Kasus Negara Nigeria dan Somalia) - Roza Nofitra Sari; Nofialdi Nofialdi; Muhammad Hizbi Islami (Al Ushuliy: Jurnal Mahasiswa Syariah dan Hukum, 2022)
This study examines the postponement of the election of the head of state from the perspective of siyasa fiqh (Case study of Nigeria and Somalia). The problem is the postponement of the election of the head of state (a case study of Nigeria and Somalia). This is different in siyasa fiqh, where in siyasa fiqh there is no stipulation on whether it is permissible to postpone the election of a head of state. From these problems, the question arises of how to postpone the election of heads of state in Nigeria and Somalia and what is the view of fiqh siyasa on postponing the elections of heads of state in Nigeria and Somalia. This research is library research. The material is obtained through books in the library, after the material is collected it is processed by searching and systematically compiling the material obtained and analyzed using the fiqh siyasa perspective. This research found that the postponement of the election of heads of state in Nigeria and Somalia was caused by problems of national defense (the Boko Haram rebellion) and the Covid-19 pandemic which spread throughout the world. Postponement of the election of the head of state has never occurred in the Al-Qur'an and As-Sunnah, as well as the system of government, and in siyasa fiqh there is also no provision for whether or not a postponement of the election of a head of state is permissible. However, in practice this has happened in the Muslim countries of Nigeria and Somalia due to the results of the ijtihad of these countries. So that the postponement of the election of the head of state is legally permissible because the results of state ijtihad make it possible because the country is in a state of emergency. So that in siyasa fiqh it is possible to postpone the election of the head of state